2020
DOI: 10.46809/jcsll.v1i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Hands: An Institutional Force in Political News Translation

Abstract: This article explores translation in news institutions. While being heavily relied on by media organizations, translation is rarely acknowledged. Translation is deeply interwoven with news in that it is used to employ ideological tendencies and political agendas. This study investigates the powerful role of media institution as a force that intervenes in producing news reports. It uses a questionnaire and interviews to see the influence of editors in the translation of news texts. For this purpose, the views o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Previous studies, in their analysis of translation manipulation, either had no focus on the agency in manipulation or assumed it to be typical of translators and editors (see Darwish, 2006; Elewa, 2019; Ethelb, 2020; Filmer, 2018; Holland, 2006; Kuo and Nakamura, 2005; Pan and Liao, 2020; Qin and Zhang, 2018). In the present study, on the other hand, the utilization of ANT, which allows for observation of the interactions and associations that produce a social entity (Latour, 2005), helped to reveal the elements whose agencies have an influence on translation manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies, in their analysis of translation manipulation, either had no focus on the agency in manipulation or assumed it to be typical of translators and editors (see Darwish, 2006; Elewa, 2019; Ethelb, 2020; Filmer, 2018; Holland, 2006; Kuo and Nakamura, 2005; Pan and Liao, 2020; Qin and Zhang, 2018). In the present study, on the other hand, the utilization of ANT, which allows for observation of the interactions and associations that produce a social entity (Latour, 2005), helped to reveal the elements whose agencies have an influence on translation manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…They assert that all of these agents, together, produce the final product: that is, the manipulated news. A small number of studies have gone beyond the textual analysis and have addressed the role of other agents involved in the process of manipulation in news translation, such as editors (Ethelb, 2020; Pan and Liao, 2020; Qin and Zhang, 2018). For example, surveying news translators and journalists, Ethelb’s (2020) study showed that editors and producers would intervene in translation through translator training, translation instructions, and textual alternations, with the aim of meeting institutional ideological policies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation